2018
DOI: 10.1002/nau.23519
|View full text |Cite
|
Sign up to set email alerts
|

ICS Educational Module: Cough stress test in the evaluation of female urinary incontinence: Introducing the ICS‐Uniform Cough Stress Test

Abstract: This module provides instructions to educate a uniform CST (the ICS-UCST), with the aim of improving the clinical practice of cough stress testing in female patients with urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 44 publications
0
26
0
2
Order By: Relevance
“…Many studies have shown that the CST is a non-invasive and easy-to-perform clinical test for the diagnosis of SUI [ 3 ]. A recent report showed that the CST has high sensitivity and specificity at different bladder fill volumes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that the CST is a non-invasive and easy-to-perform clinical test for the diagnosis of SUI [ 3 ]. A recent report showed that the CST has high sensitivity and specificity at different bladder fill volumes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient coughed forcefully 1–4 times and the examiner directly visualized the urethral meatus for the presence of leakage. Leakage of fluid from the urethral meatus occurring simultaneously with the coughs was considered a positive test [ 3 ]. Clinical SUI was diagnosed if a patient presented with involuntary urine leakage from physical activity such as coughing, sneezing or laughing and had a positive CST.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirements of this cough stress test are in keeping with the uniform Cough Stress Test endorsed by the International Continence Society. 14 A standardized pad test was also conducted with women undertaking the physical activities recommended by the International Continence Society while wearing preweighed pads. 15 If the cough stress test was negative and the increase in pad weight over the test period was less than 1 g, women were considered objectively “cured.” 11 , 16 , 17 Uroflowmetry test and measurement of the postvoid residual were performed at the end of their 12-month postoperative visit to assess voiding dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…All women included had SUI confirmed by a positive standardized cough test and had failed or declined pelvic floor muscles training. [ 19 ] Urinary incontinence was classified as recommended by the International Continence Society. [ 20 ] Preoperative assessment included women's detailed medical history, clinical, neurological and urogynecological examination.…”
Section: P Atients and M Ethodsmentioning
confidence: 99%